Measurement and propagation studies of HDTV using DVB-T2 in Singapore - Wu, Dongming (Nanyang Technological University, 2022)
This dissertation first introduces the DVB-T2 system, expounds the development status and technological innovation of the DVB-T2 system. Compare the pros and cons of DVB-T and DVB-T2 dual systems. Then, starting from the system structure of DVB-T2, analyze the principles and functions of each main module. The dissertation work is to build a complete DVB-T2 communication link for simulation, and experiment with system performance under different parameter combinations. After that, the Promax measurement tool was used for field measurement in Singapore, and the MER distribution map and C/N distribution map were drawn. Finally, compare the simulation data and field measurement data to verify the performance of the DVB-T2 system.